Biomechanics - Mohammadi, Hadi (Biomedical Engineering, 2019)
I have taught a variety of courses in biomechanics, introductory and advanced, at multiple universities in Canada. I have not been able to find or use an appropriate textbook for students whose background is not biomedical engineering. It should be noted that there are many outstanding books on biomechanics; however, they are usually not very introductory or the topics covered are too detailed, which makes it impossible for those audiences to make effective use of the book. The present book is an attempt to fill this gap. No previous familiarity of anatomy, biology, or physiology is expected, and in fact every chapter begins with a review of the relevant necessary background. Each chapter then highlights identification and explanation of the indispensable aspects of the associated biomechanics issues.